2012
DOI: 10.1016/j.stem.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Embryonic Head as a Site for Hematopoietic Stem Cell Development

Abstract: In the mouse embryo, the aorta-gonad-mesonephros (AGM) region is considered to be the sole location for intraembryonic emergence of hematopoietic stem cells (HSCs). Here we report that, in parallel to the AGM region, the E10.5-E11.5 mouse head harbors bona fide HSCs, as defined by long-term, high-level, multilineage reconstitution and self-renewal capacity in adult recipients, before HSCs enter the circulation. The presence of hemogenesis in the midgestation head is indicated by the appearance of intravascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 43 publications
(70 reference statements)
4
135
0
1
Order By: Relevance
“…A recent study showed that the mouse embryonic head also functions as a hemogenic organ to a similar extent as the AGM region, which suggests broader potential hemogenic areas in the mouse embryo; this is in agreement with previous studies showing that hemovasculogenesis also occurs in the head mesenchyme of early embryos. 13,26 The kidney is a major hemogenic organ in teleosts, such as zebrafish. Our results suggest that the mouse kidney also functions as a temporary hemogenic organ via hemovasculogenesis during early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the mouse embryonic head also functions as a hemogenic organ to a similar extent as the AGM region, which suggests broader potential hemogenic areas in the mouse embryo; this is in agreement with previous studies showing that hemovasculogenesis also occurs in the head mesenchyme of early embryos. 13,26 The kidney is a major hemogenic organ in teleosts, such as zebrafish. Our results suggest that the mouse kidney also functions as a temporary hemogenic organ via hemovasculogenesis during early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of VECadh or CD31 with the hematopoietic markers CD41 [40][41][42][43], CD45 [44] and Ter119 [45] has been used to separate endothelial from hematopoietic cells (e.g. [38,[46][47][48]), and other identification strategies have also been employed e.g. [49] [50].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…In this respect, two recent mouse studies give food for thought. Studies by Li and colleagues suggested that the head vasculature is a source of definitive HSCs [47]. Using in vitro and transplantation assays, hematopoietic potential was found to reside among Tie2 expressing cells isolated from the head.…”
Section: Hemogenic Activity -An Inherent Property Of All Young Endothmentioning
confidence: 99%
“…To confirm the in vitro result, we performed a CFU-S (colony-forming unit-spleen) assay in vivo. As shown in Figure 7C, the number of CFU-S was increased in mice infused with duplex-treated AGM cells, whereas it was To determine whether miR-142-3p is also required for the differentiation of the T-lymphoid lineage in mouse, we performed a T-cell differentiation assay in vitro [35]. Dissociated cells from the AGM region were treated with the duplex or inhibitor for 5 h. Then, the sorted cKit + CD34 + cells were co-cultured with OP9-DL1 stromal cells and cytokines for 13 days, and the CD25 + CD44 + T-cell progenitors were quantified by fluorescenceactivated cell sorting (FACS).…”
Section: Mir-142-3p Is Involved In Definitive Hematopoiesis In Mousementioning
confidence: 99%